Strengthening parental self‐efficacy and resilience: A within‐subject experimental study with refugee parents of adolescents - Eltanamly, Hend; Leijten, Patty; Roekel, Eeske; Mouton, Benedicte; Pluess, Michael; Overbeek, Geertjan (Child development, 2023)
Post‐migration stress and parenting adolescents can reduce parental self‐efficacy. This study tested the effects of strengthening parental self‐efficacy in refugee parents of adolescents and whether this makes parental self‐efficacy less impacted by post‐migration stressors. Using a within‐subject experimental design, experience sampling data were collected in 2019 from 53 refugee parents of adolescents (Mage = 39.7, SDage = 5.59, 73% Syrian, 70% mothers) in the Netherlands. Data were analyzed by dynamic structural equation modeling using interrupted time‐series analysis. The single‐session personalized intervention strengthened parental self‐efficacy (small effect: between case standardized mean difference = 0.09) and made refugee parents less vulnerable to post‐migration stressors. Findings suggest that parental self‐efficacy is malleable and strengthening it fosters refugee parents' resilience. Replications with longer‐term follow‐ups are needed.